MONITORAMENTO ESPELEOCLIMÁTICO DO TRECHO TURÍSTICO DA CAVERNA SANTANA (PETAR,SP) - Lobo, Heros Augusto Santos; Perinotto, José Alexandre De Jesus [UNESP]; Boggiani, Paulo César (Universidade Federal do Ceará, 2014)
Speleoclimate studies about Brazilian caves are still incipient and restricted tomonitoring and getting some localized measurements focused on the management of touristcaves, as well as to be used as a basis for paleoclimate studies. The present studyreflects the development of these studies in Brazil, presenting one of the most completeand detailed climatic monitoring of a cave until it is finished (2011), aiming to definethe dynamics of the atmosphere of the cave in different climatic seasons. The research wasconducted in the Santana cave, one of the most important tourist caves in Brazil. Thefield research about the monitoring of atmospheric parameters focused the air temperatureand the relative humidity. The data were submitted to a statistical treatment and ananalysis which showed that the atmosphere of the Santana cave is characterized as a warmtrap, which maintained the air in the upper galleries. Therefore, scientific parametersmay be established to its management and conservation, as well as the use of the obtainedinformation in future studies in the field of climate, paleoclimate and touristmanagement.

Los estudios del espeleoclima son incipientes en cavernas brasileñas, restringido a losestudios centrados en la gestión de las cuevas turísticas y la formación de una base parainvestigaciones paleoclimaticas. Este estudio refleja el desarrollo de este tipo deinvestigación, presentando los resultados de la investigación del clima más completa ydetallada de una cueva en Brasil hasta su finalización (2011), a fin de definir ladinámica atmosférica de una cueva y las estaciones meteorológicas. La encuesta se llevó acabo en la cueva Santana, una de las cuevas turísticas más importantes del país. Se hanllevado a cabo el seguimiento de los parámetros atmosféricos, con énfasis en latemperatura y la humedad relativa, cuyos datos fueron tratados estadísticamente. Losresultados mostraron que la atmósfera de la cueva Santana se caracteriza por ser unatrampa para atrapar el aire caliente (warm trap), que se ha mantenido en las galeríassuperiores. Por lo tanto, los parámetros pueden ser establecidos para su manejo yconservación, así como el uso de esta información para futuros estudios de huellaclimática, paleoclimatica y gestión del turismo.

Os estudos do espeleoclima ainda são incipientes em cavernas brasileiras, restrito aestudos voltados ao manejo de cavernas turísticas e como base para investigaçõespaleoclimáticas. O presente estudo reflete o desenvolvimento deste tipo de pesquisa noBrasil, apresentando os resultados de um dos mais completos e detalhados levantamentosclimáticos de uma caverna até a sua finalização (2011), com o intuito de definir adinâmica atmosférica subterrânea em diferentes estações climáticas. A pesquisa foiconduzida na caverna de Santana, uma das mais importantes cavernas turísticas do país.Foram realizados monitoramentos de parâmetros atmosféricos, com ênfase na temperatura eumidade relativa do ar. O tratamento estatístico dos resultados permitiu demonstrar que aatmosfera da caverna Santana se caracteriza como uma armadilha para a captura do ar quente(warm trap), o qual se concentra nas galerias superiores. Com isso, poderão serestabelecidos parâmetros para o seu manejo e conservação, bem como a utilização destasinformações para estudos futuros de cunho climático, paleoclimático e de manejo doturismo.
speleoclimatic monitoring of the tourist zone of Santana Cave (Petar, SãoPaulo, Brazil)
Keywords: Microclimate; Cave Atmosphere; Climate Monitoring; Speleoclimate.; Microclima; Atmosfera Cavernícola; Monitoramento Climático; Espeleoclima